English in Post-Revolutionary Iran From Indigenization to Internationalization - Borjian, Maryam (New Perspectives on Language and Education, 2013)
This book unravels the story of English, the language of 'the enemies', in post-revolutionary Iran. Drawing on diverse qualitative and quantitative fieldwork data, it examines the nation's English at the two levels of policy and practice to determine the politics, causes, and agents of the two diverging trends of indigenization/localization and internationalization/Anglo-Americanization within Iran's English education. Situating English in the nation's broader social, political, economic, and historical contexts, the volume explores the intersection of the nation's English education with variables such as power, economy, policy, ideology, and information technology over the past three decades. The multidisciplinary insights of the book will be of value to scholars of global English, education policies and reforms and language policy as well as those who are specifically concerned with education in Iran.